EXPERT SYSTEM FOR HEART DISEASE IN TYPE DIAGNOSE CARDIOVASCULAR SYSTEM THERAPY WITH MEDICATION - Siti Komariyah; Hj. Latifah, SSi, MMSI Hj. Latifah, SSi, MMSI (Jurnal Sistem Informasi, 2006)
Computers as a support tool that can solve various problems. developing various programs 'intelligent' is the effect of the business assessment to understand the ways of thinking and human behavior. Many computer experts to concentrate on the development of Artificial Intelligence (AI), which aims to make computers think and act like humans.Examples of implementation of AI is expert systems that combine knowledge and penerusuran data to solve problems that require human expertise, which aims not as a substitute for human involvement, but to substitute human knowledge into a form the system, to be used by many people.